Menumbuhkan Kesadaran dan Semangat Bela Negara Melalui Kegiatan Sosial pada Panti Asuhan Kafilul Yatim Nurul Falah - Kanza Armifa Angia Said; Rabiatuladawiyah, Adinda; Natalia, Wira; Asri, Annisa; Sinaga, Sandra Jesica; Clarensia, Sagita; Oktavia, Khalisah; Julio, Gibraldo; Fahtoni, Syahri; Muhammad, Musyaffa’; Ramadhan, Davinnizam (MADANI: Jurnal Pengabdian Kepada Masyarakat, 2023)
Every child of the nation, regardless of economic background, family, and place of residence, deserves to be given education and inspiration related to defending the country. This made the UPN "Veteran" Jakarta dedication team take the initiative to carry out socialization and social service activities for orphanage children in order to realize the next generation of the nation who have awareness and enthusiasm in defending their country. The target of this activity is 30 children at the Kafilul Yatim Nurul Falah Orphanage. This activity is divided into three stages, namely the planning, implementation, and evaluation stages. From the activities that have been carried out, it is obtained that children can understand what state defense is and how to implement it in everyday life. In addition, this activity makes children become more confident and helps them in mingling and getting to know others. This shows that socialization and charity activities at orphanages can help foster awareness and spirit of defending the country through giving attention, care, and inspiration. They can also feel valued, acquire skills and opportunities in the future, and build a positive environment. Hopefully with this activity the children can continue to grow and develop by bringing the attitude of the spirit of defending the country in the midst of society. Keywords: state defense; socialization; charity; children of the nation; orphanage